PENGARUH LABA, ARUS KAS OPERASI DAN ARUS KAS BEBAS TERHADAP DIVIDEN KAS (STUDI PADA EMITEN MANUFAKTUR DI BURSA EFEK INDONESIA) - Jen Surya (InFestasi, 2010)
The aim of this research is to examine and analyze the influence of   net income, operation cash flow, and free cash flow both simultaneously   and partially in manufacturing companies listed in Indonesian Stock Exchange (ISE). Observation periods  from 2001 until 2005. The type of  research used in verification research or research to verify hypothesis with simple random sampling.The object of population are  manufacturing industries which listed in Jakarta Stock Exchange that has net income, the positive operation cash flow, the positive free cash flow and paid cash dividend. This research sample 109 population. To aimed influence net income, the positive operation cash flow, and the positive free cash flow both simultaneously and partially use multiple regression.Result of this research show that; (1) net income has a significant influence    on cash dividend, (2) the positive operation cash flow has a significant influence on cash dividend, (3) the positive free cash flow ha a significant negative  influence on cash dividend, and (4)  simultaneously net income,  operation cash flow, and free cash flow  has a significant  influence on cash dividend.